2017
DOI: 10.1590/s1806-37562016000000190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure on blood pressure in patients with resistant hypertension and obstructive sleep apnea: a systematic review and meta-analysis of six randomized controlled trials

Abstract: Objective: To evaluate systematically the effects of continuous positive airway pressure (CPAP) on blood pressure in patients with resistant hypertension and obstructive sleep apnea (OSA). Methods: The Cochrane Library, PubMed, ScienceDirect, and the Web of Science were searched for studies investigating the effects of CPAP on blood pressure in patients with resistant hypertension and OSA. The selected studies underwent quality assessment and meta-analysis, as well as being tested for heterogeneity. Results: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
0
19
0
3
Order By: Relevance
“…OSAHS is a potential major risk factor for the morbidity and mortality of many cardiovascular complications 2 , such as hypertension, arrhythmias, myocardial infarction, heart failure, ventricular hypertrophy, systolic and diastolic dysfunctions, as well as stroke 3,4 . OSAHS is associated with a significantly higher risk of hypertension and is regarded as an independent risk factor for hypertension 5 . Evidence indicated that the cardiac dysfunction and cardiomyocyte injury was detected in OSAHS patients and animal modes 6,7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OSAHS is a potential major risk factor for the morbidity and mortality of many cardiovascular complications 2 , such as hypertension, arrhythmias, myocardial infarction, heart failure, ventricular hypertrophy, systolic and diastolic dysfunctions, as well as stroke 3,4 . OSAHS is associated with a significantly higher risk of hypertension and is regarded as an independent risk factor for hypertension 5 . Evidence indicated that the cardiac dysfunction and cardiomyocyte injury was detected in OSAHS patients and animal modes 6,7 .…”
mentioning
confidence: 99%
“…It has been shown that OSAHS treatment might reduce the risk of cardiovascular complications. CPAP treatment has been proven to reduce blood pressure 5,20 and correct left ventricular hypertrophy and systolic and diastolic dysfunctions caused by OSAHS 21,22 . There were limited data on the effects of oral appliance treatment on cardiac function.…”
mentioning
confidence: 99%
“…Treatment of OSA with continuous positive airway pressure (CPAP) therapy has shown beneficial effects in patients with cardiovascular disorders (Maeder, Schoch, & Rickli, 2016). CPAP treatment decreases blood pressure in patients with resistant hypertension (Lei et al, 2017) and improves heart function in patients with heart failure (Sun, Shi, Li, & Chen, 2013). There is evidence that CPAP treatment decreases the activity of the sympathetic nervous system (Fatouleh et al, 2015) and oxidative stress (Tichanon et al, 2016), which play a crucial rule in the development of arrhythmia in patients with OSA (Bitter, Fox, Gaddam, Horstkotte, & Oldenburg, 2015).…”
mentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials indicated reductions in mean systolic blood pressure of 5.4 mm Hg and diastolic blood pressure of 3.86 mm Hg after CPAP in those with resistant hypertension and OSA. 58 Weight loss has been shown to reduce the AHI and other parameters related to sleep apnea such as oxygen desaturation index in patients with obesity and diabetes. 59 Weight loss combined with CPAP compared with CPAP or weight loss alone showed an incremental benefi t in improving glucose parameters, triglycerides, and possibly systolic blood pressure and triglycerides.…”
Section: Effect Of Treatment For Osa On Metabolic Syndromementioning
confidence: 99%